Durability Map for The Friction Stir Welding Tools with Flat Faced Pins - J, Stephen Leon; G, Bharathiraja; V, Jayakumar (International Journal of Integrated Engineering, 2020)
In friction stir welding, tools made with flat faced pins deliver comparatively higher strength joints than circular pins. However, its non-axisymmetric cross section about the rotational axis results in fluctuating stress along its surface that leads to premature tool failure. This requires a systematic definition for process parameter selection domain based on the number of flat faces in the pin to improve tool life. Temperature dependent strength of the material to be joined in the stir zone is the only source of opposing force for the tool movement. To predict opposing force, temperature gradient developed by the different levels of process parameters in the stir zone is numerically quantified with an experimentally validated model. Based on the estimated temperature, maximum stress acting on the tool pin is quantified with a remodified temperature dependent analytical model. The effect of increase in process temperature on the strength of the weld joint is experimentally analysed through the investigation of change in hardness value in heat affected zone. Obtained results are used to develop tool durability maps for tools with flat faced pin in a domain on which higher and lower limits are fixed by considering satisfactory level of joint strength and tool life respectively. These maps provide flexibility in the parameter selection with an acceptable level of compromise in joint strength or in tool life based on the quality requirement of weld joint.